Analisis Aspek Linier Morfometrik Sub-DAS Lahundape Menggunakan Teknologi Sistem Informasi Geografis (SIG) pada Wilayah Kota Kendari - Suryawan Asfar; Ali Okto; Andi Makkawaru; Mirnayanti Karim (Jurnal Rekayasa Geofisika Indonesia, 2020)
This research activity was carried out in the Lahundape Sub-watershed, using morphometric linear analysis where the analysis was carried out by extracting river networks using digital elevation data, namely Digital Elevation Model (DEM). From the results of data processing and analysis which found that the area of the Lahundape Sub-basin reaches 6.97 km2, the circumference of the Lahundape Sub-basin area reaches 23.74 km, the length of the Lahundape Sub-watershed reaches 6.91 km, the width of the Lahundape Sub-Basin reaches 1.01 km. The Lahundape Sub-watershed has a total of 5 river orders with a total number of rivers as much as 917, the length of the river flow The Lahundape Sub-watershed has increased in order 1 and decreased to order 5, with an average value of river length between 0.06 km up to 0.78 km and the total Lsm value reaches 1.73 km. The length of the river flow ratio of each order has increased were for the 2nd order/1st order (II/I) of 0.45 km, 3rd order/2nd order (III/II) of 0.46 km, 4th order/3rd order (IV/III) of 0.72 km, 5th order/4th order (V/IV) of 0.87 km. The Lahundape Sub-watershed river branching ratio has an average value of 3.42, where for the value of 1st order/2nd order of 4.72, 2nd order/3rd order of 4.31, 1st order 3/4th order of 2.92, and for 4thorder/5th order of 1.71.